Psychological distress, understanding of cancer and illness uncertainty in patients with Cancer of Unknown Primary. Issue 11 (3rd July 2022) - Wolyniec, Kamil; Sharp, Jessica; Fisher, Krista; Tothill, Richard W.; Bowtell, David; Mileshkin, Linda; Schofield, Penelope
Abstract: Objective: Patients diagnosed with Cancer of Unknown Primary (CUP) experience high levels of psychological distress and report poor understanding of their cancer. We aimed to investigate: (1) if CUP patients with poorer understanding of their cancer diagnosis and testing experience more symptoms of psychological distress than those with better understanding; (2) if the relationship between patients' understanding of their cancer and psychological distress is mediated by illness uncertainty; and (3) explore whether patients' degree of understanding of their cancer can be predicted by clinical and socio‐demographic factors. Methods: 209 CUP patients completed a questionnaire measuring anxiety, depression, illness uncertainty, fatigue, pain, sleep and understanding of their cancer. Using an apriori theoretical framework, we employed structural equation modelling to investigate predictors of patient's understanding of their cancer and psychological distress and the relationships between understanding, illness uncertainty and distress. Results: The structural equation model displayed good fit indices and supported the hypothesised relationship of patient's understanding of their cancer and the extent of psychological distress, which was mediated via illness uncertainty. Physical symptoms were positively associated with psychological distress and illness uncertainty. Younger age was predictive of lower patient's understanding of their cancer and higher levels of psychological distress. Conclusions: Patients with CUP, particularly those who are younger and experiencing more physical symptoms, report higher levels of psychological distress and may require additional mental health support. Our findings highlight a need to improve CUP patient's understanding about their illness, which could help reduce their illness uncertainty and alleviate psychological distress.